A systematic scoping review of the use of surfactant replacement therapy for respiratory distress syndrome in preterm neonates in low- and middle-income countries - Price, Caris A.; Tooke, Lloyd; Zar, Heather J.; Morrow, Brenda M. (Frontiers in Pediatrics, 2025)
IntroductionThe availability and use of surfactant replacement therapy (SRT) for respiratory distress syndrome (RDS) in low- and middle-income countries (LMICs) is variable with unclear impact on infant outcomes. This review evaluates the published evidence on SRT in the management of preterm neonates with RDS in LMICs, with a focus on SRT availability, administration, timing, type, and cost.MethodsA systematic scoping review of seven databases was conducted, following the Preferred Items for Systematic Reviews and Meta-Analysis guidelines extension for Scoping Reviews. English language systematic reviews and observational and experimental studies, published between January 2010 and July 2023, were eligible for this review. Case reports, small case series, and qualitative studies were excluded. Titles and abstracts were screened by one reviewer and full text by two independent researchers. Sufficiently homogeneous randomized controlled trials (RCTs) were synthesized using random-effects meta-analyses, while other results were synthesized narratively. Primary outcomes for meta-analyses were (1) need for invasive mechanical ventilation (IMV), (2) development of bronchopulmonary dysplasia (BPD), and (3) in-hospital mortality.ResultsAfter screening 483 titles/abstracts and 266 full texts, 113 articles were included in the final review (52 RCTs, 50 observational studies, and 11 systematic reviews). Studies reported both INtubation-SURfactant-Extubation (INSURE) and Less/Minimal Invasive Surfactant Administration/Treatment (LISA/MIST) methods of SRT, with different threshold criteria for implementation. There was moderate certainty evidence that using LISA/MIST reduced the need for IMV [risk difference (RD): 0.10 (95% confidence interval, CI: 0.04–0.17); p = 0.001] compared with INSURE, with a borderline effect on BPD [RD: 0.04 (95% CI: 0.00–0.08); p = 0.05] and no significant effect on mortality [RD: 0.01 (95% CI: −0.02 to 0.04; p = 0.5)]. There was low certainty evidence that poractant alfa (200 mg/kg) was associated with a reduced need for mechanical ventilation compared with beractant (100 mg/kg) (RD 0.10 (95% CI: 0.02–0.18); p = 0.01), with a similar reduction in mortality [RD: 0.07 (95% CI: 0.01–0.13); p = 0.02]. No cost-effectiveness studies were identified.ConclusionLISA/MIST should be used in preference to INSURE. Poractant alfa (200 mg/kg) is conditionally recommended in preference to beractant (100 mg/kg). Regionally relevant cost-effectiveness studies are needed.